The abiding, hidden, and pervasive centrality of the health research workforce - Paulo Ferrinho; Michael Makanga; Shabnum Sarfraz; Mario Dal Poz (BMC, 2023)
Abstract Research for health and development (R4HD) acknowledges that many of the determinants of health lie outside the boundaries of the health system. The size and quality of the health and care workforce (HCWF) are key drivers towards the future trajectory of many of these factors. We consider researchers for health and development an abiding, pervasive but neglected constituent part of this HCWF. This workforce straddles many professional groups and sectors. The diversity of occupations, lack of standardization in occupational cadres, the complexity and gendered aspects of the labour market, and the variable demographic, epidemiological, socio-economic and health systems' contexts in the global south and the global north, led to a kaleidoscopic perception of the health research workforce that have kept it hidden from public opinion. This led to neglect by science as well as health policymakers and created an orphan sub-set of the HCWF. Understanding the health researchers' labour market will help to identify means to develop, retain and utilize the health research workforce, addressing size, composition, role, skills transferability, careers and social impact through building, enabling or sustaining its research functions, capacity, employment opportunities and career tracks, among other issues. This thematic series of the Human Resources for Health Journal, calls for papers that go beyond narrow conceptual approaches and professional understandings of health care workers and the health research workforce, and requests that contributors examine important workforce issues through the broad lens of R4HD within a sustainable development goals framework.